The Interaction Between Autophagy and JAK/STAT3 Signaling Pathway in Tumors - Xu, Jiangyan; Zhang, Jinrong; Mao, Qi-Fen; Wu, Jian; Wang, Yuan (Frontiers in Genetics, 2022)
Tumor is one of the important factors affecting human life and health in today's world, and scientists have studied it extensively and deeply, among which autophagy and JAK/STAT3 signaling pathway are two important research directions. The JAK/STAT3 axis is a classical intracellular signaling pathway that assumes a key role in the regulation of cell proliferation, apoptosis, and vascular neogenesis, and its abnormal cell signaling and regulation are closely related to the occurrence and development of tumors. Therefore, the JAK/STAT3 pathway in tumor cells and various stromal cells in their microenvironment is often considered as an effective target for tumor therapy. Autophagy is a process that degrades cytoplasmic proteins and organelles through the lysosomal pathway. It is a fundamental metabolic mechanism for intracellular degradation. The mechanism of action of autophagy is complex and may play different roles at various stages of tumor development. Altered STAT3 expression has been found to be accompanied by the abnormal autophagy activity in many oncological studies, and the two may play a synergistic or antagonistic role in promoting or inhibiting the occurrence and development of tumors. This article reviews the recent advances in autophagy and its interaction with JAK/STAT3 signaling pathway in the pathogenesis, prevention, diagnosis, and treatment of tumors.